Amygdaloid involvement in the defensive behavior of mice exposed to the open elevated plus-maze - Sorregotti, Tatiani [UNESP] (2018)
Previous studies have shown that the exposure to an open elevated plus maze (oEPM, an EPM with all four open arms) elicits fear/anxiety-related responses in laboratory rodents. However, very little is known about the underlying neural substrates of these defensive behaviors. Accordingly, the present study investigated the effects of chemical inactivation of the amygdala [through local injection of cobalt chloride (CoCl2: a nonspecific synaptic blocker)] on the behavior of oEPM-exposed mice. In a second experiment, the pattern of activation of the basolateral (BLA) and central (CeA) nuclei of the amygdala was assessed through quantification of Fos protein expression in mice subjected to one of several behavioral manipulations. To avoid the confound of acute handling stress, 4 independent groups of mice were habituated daily for 10 days to an enclosed EPM (eEPM) and, on day 11 prior to immunohistochemistry, were either taken directly from their home cage (control) or individually exposed for 10 min to a new clean holding cage (novelty), an eEPM, or the oEPM. An additional group of mice (maze-naïve) was not subjected to either the habituation or exposure phase but were simply chosen at random from their home cages to undergo an identical immunohistochemistry procedure. Results showed that amygdala inactivation produced an anxiolytic-like profile comprising reductions in time spent in the proximal portions of the open arms and total stretched attend postures (SAP) as well as increases in time spent in the distal portions of the open arms and total head-dipping. Moreover, Fos-positive labeled cells were bilaterally increased in the amygdaloid complex, particularly in the BLA, of oEPM-exposed animals compared to all other groups. These results suggest that the amygdala (in particular, its BLA nucleus) plays a key role in the modulation of defensive behaviors in oEPM-exposed mice.